2020
DOI: 10.33312/ijar.459
|View full text |Cite
|
Sign up to set email alerts
|

Earnings Management in the Pre and Post eXtensible Business Reporting Language Period in Indonesia

Abstract: This study aims to determine and analyze the impact of XBRL adoption on earnings management conducted by company management in Indonesia. Earnings management in this study is proxied by discretionary accruals. The population of this research is manufacturing companies listed on the Indonesia Stock Exchange. The research sample was selected using the purposive sampling method, and the resulted total sample of this research is 15 manufacturing companies. This research period includes the period before the adopti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Although the literature on XBRL is vast, to the best of our knowledge not much attention has been paid to investigating the effect of XBRL adoption on earnings management. Chen, Guo, Liu, and Tong (2021) Peng, Shon, and Tan (2011) found that adoption of XBRL encourage companies to engage less in earnings manipulations; Kim, Kim, and Lim (2019) found that absolute discretionary accruals decrease significantly from the pre-XBRL period to the post-XBRL period, indicating that adoption of XBRL restricts earnings management and significantly reduces the levels of discretionary accruals; Mayapada, Afdhal, and Syafitri (2020) found that adoption of XBRL reduces the level of earnings management, and thus reduces opportunistic behavior of management in financial reporting. Furthermore, Hsieh, Wang, & Abdolmohammadi (2019) found that the implementation of XBRL is positively related to earnings release efficiency of companies with good news.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although the literature on XBRL is vast, to the best of our knowledge not much attention has been paid to investigating the effect of XBRL adoption on earnings management. Chen, Guo, Liu, and Tong (2021) Peng, Shon, and Tan (2011) found that adoption of XBRL encourage companies to engage less in earnings manipulations; Kim, Kim, and Lim (2019) found that absolute discretionary accruals decrease significantly from the pre-XBRL period to the post-XBRL period, indicating that adoption of XBRL restricts earnings management and significantly reduces the levels of discretionary accruals; Mayapada, Afdhal, and Syafitri (2020) found that adoption of XBRL reduces the level of earnings management, and thus reduces opportunistic behavior of management in financial reporting. Furthermore, Hsieh, Wang, & Abdolmohammadi (2019) found that the implementation of XBRL is positively related to earnings release efficiency of companies with good news.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The implementation of XBRL utilization in Indonesia has generally been mandated by several government agencies such as the Bank of Indonesia (BI) as well as and the Financial Services Authority (FSA) and Indonesia Stock Exchange (ISE) (see, e.g., Wijanarko and Moedjiono, 2015;Mayapada et al, 2020). The existence of XBRL in Indonesia was first carried out by the Bank of Indonesia (BI).…”
Section: Development Of Xbrl In Indonesiamentioning
confidence: 99%
“…The Indonesian Journal of Accounting Research -May, Vol. 24, No.2, 2021 the sub-cluster of the influence of XBRL in accounting and corporate governance, there is information related to earnings management, information asymmetry, financial information environment, and information risk (see, e.g., Mayapada et al, 2020;Pamungkas and Kristanto, 2019;Tohang et al, 2020;Zamroni and Aryani, 2018), on XBRL sub-cluster in auditing (see, e.g., Saputro and Achjari, 2020), and in the XBRL sub-cluster on the factors of decision-making or related to market reaction (see, e.g., Jayani et al, 2020;Junus and Irwanto, 2021).…”
Section: Xbrl's Educationmentioning
confidence: 99%
See 2 more Smart Citations